2013
DOI: 10.1038/nature12331
|View full text |Cite
|
Sign up to set email alerts
|

Treg induction by a rationally selected mixture of Clostridia strains from the human microbiota

Abstract: Manipulation of the gut microbiota holds great promise for the treatment of inflammatory and allergic diseases. Although numerous probiotic microorganisms have been identified, there remains a compelling need to discover organisms that elicit more robust therapeutic responses, are compatible with the host, and can affect a specific arm of the host immune system in a well-controlled, physiological manner. Here we use a rational approach to isolate CD4(+)FOXP3(+) regulatory T (Treg)-cell-inducing bacterial strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

58
2,049
9
25

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,467 publications
(2,141 citation statements)
references
References 27 publications
58
2,049
9
25
Order By: Relevance
“…However, MWAS have produced long lists of implicated microbes without clearly elucidating their causal role, correlations have not always held up in subsequent studies, and notable differences have been observed between human and animal studies 13 . Although many correlations may simply reflect biomarkers of disease, causal links between the microbiome and disease susceptibility have been sporadically defined in studies that have initially identified immunomodulatory bacteria, functionally categorized the microbiota on the basis of immune recognition, or used complex bioinformatic heuristics to identify disease-modulating bacteria 611 . Ultimately, a generalizable pathway that refines the catalog of differentially abundant microbes identified by MWAS to include only those most likely causally related to the phenotype is lacking.…”
Section: Main Textmentioning
confidence: 99%
“…However, MWAS have produced long lists of implicated microbes without clearly elucidating their causal role, correlations have not always held up in subsequent studies, and notable differences have been observed between human and animal studies 13 . Although many correlations may simply reflect biomarkers of disease, causal links between the microbiome and disease susceptibility have been sporadically defined in studies that have initially identified immunomodulatory bacteria, functionally categorized the microbiota on the basis of immune recognition, or used complex bioinformatic heuristics to identify disease-modulating bacteria 611 . Ultimately, a generalizable pathway that refines the catalog of differentially abundant microbes identified by MWAS to include only those most likely causally related to the phenotype is lacking.…”
Section: Main Textmentioning
confidence: 99%
“…Clostridium species in human gut can influence the balance between Th17 and regulatory T cells (Treg) 5. These observations, when taken together with our previous studies showing proinflammatory T‐cell polarization and cross‐reactivity between AQP4 and ABC‐TP in NMO, highlighted the need to evaluate the proposed connection between C. perfringens and NMO pathogenesis.…”
mentioning
confidence: 87%
“…L'étude de souris gnotoxéniques montre aussi que la nature et l'intensité des réponses immunes adaptatives dépendent de la composition du microbiote et particulièrement de la présence de la bactérie segmentée filamenteuse (SFB) [42] (➜). Contrairement à la majorité des bactéries commensales 5 qui induisent une réponse IgA relativement modeste et des réponses T dominées par des réponses T régulatrices, notamment dans le côlon [18,[26][27][28], la SFB joue un rôle privilégié dans la maturation post-natale des réponses immunes innées et adaptatives chez son hôte [18,22] (Figure 2). Cette bactérie, cultivable seulement récemment [29], est apparentée au genre des Clostridium [30].…”
Section: Synthèse Revuesunclassified